Deskripsi Kasus Learning Loss Pada Anak Usia Dini Kelompok B - Beatrix Ibrahim; Laiya, Sri Wahyuningsi; Jamin, Nunung Suryana (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
Based on the findings and discussion, it can be concluded that the Case Description of Learning Loss among children in Group B at TK Pembina Kindergarten in Kota Tengah District, Gorontalo City has a possibility of optimal development. This was evident from the four indicators; language, social, cognitive, and artistic aspects, where 6 out of 15 children experienced Learning Loss. This was proven by the lack of awareness from parents to allocate more time for children to explore their self-confidence, both at home and school, which was still not optimal. Such situations are also influenced by the role of teachers, who should pay more attention to the children in the classroom so they do not feel neglected, as teachers are the key to children's success. There are four aspects that serve as indicators for teachers to assess the development of knowledge in each child; social-emotional, artistic, cognitive, and language aspects.